The high price of money : an interpretation of world interest rates - Ciocca, Pierluigi; Nardozzi, Giangiacomo; Levy, Aviram (Oxford [England] : Clarendon Press ; New York : Oxford University Press, 1996)
The argument of this accessible monograph is that, contrary to prevailing opinion, high interest rates are not a fact of economic life. The authors argue that this is a conventional assumption rooted in the expectations of financial markets. World economic evidence from the last twenty years indicates that conscious policies are, in fact, capable of altering interest rates in the short term, without heavy costs. Such policies must be devised and pursued if we are to come out of recession.
"This English edition contains a new chapter (Chapter 7)--Preamble.
Includes bibliographical references.
gau 04/08/2016
Loans
Keywords: Interest rates; Economic policy